Impact of a Combined Philosophy and Mindfulness Intervention on Positive and Negative Indicators of Mental Health Among Pre-kindergarten Children: Results From a Pilot and Feasibility Study - Malboeuf-Hurtubise, Catherine; Lefrançois, David; Mageau, Geneviève A.; Taylor, Geneviève; Éthier, Marc-André; Gagnon, Mathieu; DiTomaso, Carina (Frontiers in Psychiatry, 2020)
Background: Research on mindfulness and philosophy for children (P4C) has yielded promising results regarding innovative interventions that may be implemented in elementary school settings to foster greater child resiliency and wellbeing (Mak, Whittingham, Cunnington, & Boyd, 2017; Malboeuf-Hurtubise & Lacourse, 2016; Zenner, Herrnleben-Kurz, & Walach, 2014). Goal: The goal of this feasibility study was to pilot a new intervention, which combines mindfulness meditation and P4C activities, with the goal of improving mental health in pre-kindergarten children, assessed with positive (i.e. social skills and adaptability) and negative (i.e. internalized symptoms, comprises depression, anxiety, inattention; and hyperactivity) indicators. Methods: A randomized cluster trial with a wait-list control group was employed to evaluate the impact of the combined MBI and P4C intervention on child mental health. Two classrooms of pre-kindergarten children (N = 38, mean age = 4.6 years old) took part in this study and were randomly allocated to the experimental or wait-list control conditions. Teachers completed pre- and post-intervention questionnaires. Results: ANCOVAs did not reveal a significant effect of condition on internalized symptoms, controlling for baseline levels. Sensitivity analyses indicated that for the whole sample, internalized symptom scores were statistically significantly lower at post-intervention, when compared to pre-intervention scores. No impact of group on levels of hyperactivity was found, however, sensitivity analyses indicated that for both the experimental and control groups, hyperactivity scores were statistically significantly lower at post-intervention, when compared to pre-intervention scores. Finally, no impact of group on levels of social skills and adaptability were found. Sensitivity analyses conducted using paired t-tests did not indicate statistically significant pre-to-post changes in scores for both variables Conclusion: These preliminary results suggest that mindfulness and philosophy for children may not be the most effective intervention to foster short-term resiliency, wellbeing and better mental health in children. Further research considering the impact of moderators such as age or baseline levels of psychopathology, using longer time frames and comparing the effectiveness of this combined intervention with other types of school-based interventions with similar aims is warranted, to evaluate if mindfulness and P4C interventions have an added value compared to other interventions in school settings.